(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2026)
This article describes the theoretical and practical aspects of increasing sports motivation among students. Factors affecting students’ regular participation in sports, types of motivation and effective ways of encouraging them were analyzed. Also, recommendations on the development of sports activities in higher educational institutions were developed.